The cocoa industry in Malaysia - Abdul Aziz Abdul Rahman (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1990)
There has been a growing concern about the impact of economic policies on agriculture, especially among developing countries. This is primarily because these policies - including pricing, taxation and trade policies - directly and indirectly affect the profitability and level of properity in the agriculture sector. It is with this in mind that the Kiel Institute of World Economics has embarked on a Research Project to evaluate how policies in developing countries affect their agriculture sectors. This is planned to be achieved using two approaches, namely, a qualitative cross-section analysis of agricultural protection for a fairly large number of developing countries, and a detailed analysis for three developing countries. Malaysia has been selected to represent one of the three developing countries which is to be analysed in greater detail. This paper presents parts of the findings of the Subproject on The Magnitude and Structure of Agricultural Price Protection in Malaysia. It traces the historical development of the cocoa industry in Malaysia, with emphasis on the policies which have been instrumental in moulding its growth.
Keywords: 330; Kakao; Malaysia